Self-assembled biophotonic lasing network driven by amyloid fibrils in microcavities - Gong, Chaoyang (2022)
Self-assembled biological structures have played a significant role in many living systems for its functionality and distinctiveness. Here, we experimentally demonstrate that the random dynamic behavior of strong light-matter interactions in complex biological structures can provide hidden information on optical coupling in a network. The concept of biophotonic lasing network is therefore introduced, where a self-assembled human amyloid fibril network was confined in a Fabry-Perot optical cavity. Distinctive lasing patterns were discovered from self-assembled amyloids with different structural dimensions (0D, 1D, 2D, and 3D) confined in a microcavity. Network laser emission exhibiting evidence of light coupling at different wavelengths and locations was spectrally resolved. Dynamic changes of lasing patterns can therefore be interpreted into a graph to reveal the optical correlation in biophotonic networks. Our findings indicate that each graph represents the highly unclonable features of a self-assembled network which can sensitively respond to environmental stimulus. This study offers the potential for studying dynamic biological networks through amplified interactions, shedding light on the development of biologically controlled photonic devices, biosensing, and information encryption.